Identification of sources of resistance among potato breeding material against stem nematode - Pysarenko, N.; Zakharchuk, N.; Hordiienko, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To identify new sources of resistance against stem nematode among potato breeding material and provide recommendations for the involvement of the most promising genotypes in breeding practice.Methods. The research was conducted in the breeding laboratory of the Polissia Research Department of the Institute for Potato Research, during 2018—2022, with promising source material of its own potato breeding, interspecific hybrids of the laboratory of genetic resources of the Institute for Potato Research and potato varieties and studied their resistance to stem nematode on an infectious background.Results. It was found that among the studied hybrid potato material, up to 9% of highly resistant forms, about 15—29% with relatively high and 41—62% of genotypes with moderate resistance were distinguished. Among the evaluated potato varieties, only a small number demonstrate high resistance, while the majority exhibit moderate resistance to the nematode. Sources with high, relatively high and moderate resistance to the nematode among promising potato hybrids were identified. Selected genotypes are the following: G.10.7/13, P.14.17-14, P.15.5/27, G.09.8-14, Z.14.64/3, P.13.26/13, G.08.194/122, Z.14.64-2, G.15.1-3, Z.14.49-7 and P.14.43-18 combine resistance to stem nematode with high expression of the main economically valuable traits. It was found that the breeding material that showed moderate resistance to the nematode was created with the participation of potato varieties: Santarka, Radomysl, Irbytskyi, Podoliia, Bellarossa, Satina, Tyras, Vektar and Hurman. As a result of targeted breeding work, three new potato varieties have been created: Fanatka, Rostavytsia and Dzhavelina, characterised by high productivity, drought tolerance, and resistance to stem nematode and quarantine microorganisms.Conclusions. We recommend using the selected stem nematode-resistant hybrids in breeding work to develop resistant potato varieties. To limit the spread and development of the nematode, we recommend cultivating the suggested resistant potato varieties.